Recyclable vitrimer-based printed circuit boards for sustainable electronics - Zhang, Zhihan; Biswal, Agni K.; Nandi, Ankush; Frost, Kali; Smith, Jake; Nguyen, Bichlien; Patel, Shwetak; Vashisth, Aniruddh; Iyer, Vikram (Nature Sustainability, 2024)
Printed circuit boards (PCBs) are ubiquitous in electronics and make up a substantial fraction of environmentally hazardous electronic waste when devices reach end-of-life. Their recycling is challenging due to their use of irreversibly cured thermoset epoxies in manufacturing. Here, to tackle this challenge, we present a PCB formulation using transesterification vitrimers (vPCBs) and an end-to-end fabrication process compatible with standard manufacturing ecosystems. Our cradle-to-cradle life-cycle assessment shows substantial environmental impact reduction of the vPCBs over conventional PCBs in 11 categories. We successfully manufactured functional prototypes of Internet of Things devices transmitting 2.4 GHz radio signals on vPCBs with electrical and mechanical properties meeting industry standards. Fractures and holes in vPCBs are repairable while retaining comparable performance over multiple repair cycles. We further demonstrate a non-destructive recycling process based on polymer swelling with small-molecule solvents. Unlike traditional solvolysis recycling, this swelling process does not degrade the materials. Through dynamic mechanical analysis, we find negligible catalyst loss, minimal changes in storage modulus and equivalent polymer backbone composition across multiple recycling cycles. This recycling process achieves 98% polymer recovery, 100% fibre recovery and 91% solvent recovery to create new vPCBs without performance degradation. Overall, this work paves the way for sustainability transitions in the electronics industry.